Respuesta :
Start with
[tex]-2z+10+7z=16z+7[/tex]
Simplify the left hand side by summing like terms (the one involving z):
[tex]5z+10 = 16z+7[/tex]
Subtract 5z from both sides:
[tex]10 = 11z+7[/tex]
Subtract 7 from both sides
[tex]3 = 11z[/tex]
Divide both sides by 11:
[tex]z = \dfrac{3}{11}[/tex]
The equation has one solution and the solution is z = 3/11.
What is simplification of an equation?
Simplification of an equation is the process of writing an equation in the most efficient and compact form without affecting the value of the original equation.
For the given situation,
The equation is -2z+10+7z=16z+7
The equation can be simplified as
⇒ [tex]-2z+10+7z=16z+7[/tex]
⇒ [tex]-2z+7z-16z=7-10[/tex]
⇒ [tex]-11z=-3[/tex]
⇒ [tex]z=\frac{-3}{-11}[/tex]
⇒ [tex]z=\frac{3}{11}[/tex]
Hence we can conclude that the equation has one solution and the solution is z = 3/11.
Learn more about simplification of an equation here
https://brainly.com/question/11444405
#SPJ2